Performance, usability and comparison of two versions of a new macular vision test: the handheld Radial Shape Discrimination test - Jae Y. Ku; Ashli F. Milling; Noelia Pitrelli Vazquez; Paul C. Knox (PeerJ, 2016)
Background Central vision, critical for everyday tasks such as reading and driving, is impacted by age-related changes in the eye and by diseases such as age-related macular degeneration. The detection of changes in macular function is therefore important. The Radial Shape Discrimination (RSD) test measures the threshold at which distortions in a radial frequency pattern can be detected and there is evidence that it is more sensitive to macular pathology than visual acuity (VA). It also provides a more quantitative measure of macular function than the commonly available Amsler grid. Recently, handheld versions of the test (hRSD) in which stimuli are presented on mobile devices (e.g., Apple iPod Touch, iPhone) have been developed. We investigated the characteristics of the hRSD test in healthy participants. Methods Data were collected using both three-alternative forced choice (3AFC) and 4AFC versions of the hRSD test, presented on an Apple iPod Touch. For the 3AFC version, data from a single test session were available for 186 (72 male; mean ± SD age 42 ± 17y; range 16–90y) healthy participants. Test-retest data were available for subgroups of participants (intra-session: N = 74; tests approximately 2 months apart: N = 30; tests 39 months apart: N = 15). The 3AFC and 4AFC versions were directly compared in 106 participants who also completed a usability questionnaire. Distance and near VA and Pelli Robson Contrast Sensitivity (CS) data were collected and undilated fundoscopy performed on the majority of participants. Results Mean (±SD) 3AFC hRSD threshold was −0.77 ± 0.14 logMAR, and was statistically significantly correlated with age (Pearson r = 0.35; p < 0.001). The linear regression of hRSD threshold on age had a slope of +0.0026 compared to +0.0051 for near VA (which also correlated with age: r = 0.51; p < 0.001). There were no statistically significant differences in hRSD thresholds for any of the test-retest subgroups. We also observed no statistically significant difference between 3AFC (−0.82 ± 0.11 logMAR) and 4AFC (−0.80 ± 0.12 logMAR) hRSD thresholds (t = 1.85, p = 0.067) and participants reported excellent test usability with no strong preference expressed between the 3AFC and 4AFC versions of the test. Discussion The 3AFC hRSD thresholds we report are consistent with a number of previous studies, as is its greater stability in ageing compared to VA. We have also shown that in the absence of pathology, thresholds are stable over short and long timescales. The 4AFC thresholds we have reported provide a baseline for future investigations, and we have confirmed that 3AFC and 4AFC thresholds are similar, providing a basis of comparisons between studies using the different versions. As the hRSD test is easy to use and relatively inexpensive, clinical studies are now required to establish its ability to detect and monitor macular pathologies.